Jumlah Neutrofil sebagai Penanda Inflamasi pada Diabetes Melitus Tipe 2 dengan dan tanpa Ulkus - Aprilia Anjarwati; Elfred Rinaldo Kasimo; Dita Apriana Dwi Astuti (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2026)
Type 2 diabetes mellitus causes chronic hyperglycemia, systemic inflammation, and immune dysfunction, which increase the risk of diabetic foot ulcers, amputation, and mortality. This study is urgent because the dominance of elevated neutrophil counts in T2DM patients with ulcers reflects an active inflammatory response that may worsen wound healing, while neutrophil testing is widely available in clinical pathology laboratories. The literature highlights the role of inflammation, cytokines, NLR, and complex biomarkers in diabetic complications; however, these indicators are often costly, less applicable in regional healthcare settings, and rarely compare ulcerated and non-ulcerated T2DM patients directly. This study addresses this gap by proposing absolute neutrophil count as a simple, quantitative, and categorical inflammatory indicator. The objective was to analyze differences in neutrophil counts between T2DM patients with and without ulcers at RSU Daha Husada Kediri using a comparative descriptive quantitative design involving 20 patients. The results showed that 80% of ulcerated T2DM patients had elevated neutrophil levels compared with 10% in the non-ulcer group, with a significantly higher mean neutrophil count (9.19 ± 2.56 vs 4.80 ± 1.32 ×10³/µL; p = 0.00012). In conclusion, increased neutrophil counts significantly distinguish the inflammatory status of T2DM patients with ulcers and represent a practical clinical marker for early screening of diabetic foot ulcer complications in regional hospitals.